Nanoscale Self-Assembly for Therapeutic Delivery - Yadav, Santosh; Sharma, Ashwani Kumar; Kumar, Pradeep (Frontiers in Bioengineering and Biotechnology, 2020)
Self-assembly is the process of association of individual units of a material into highly arranged/ordered structures/patterns. It imparts unique properties to both inorganic and organic structures, so generated, via non-covalent interactions. Currently, self-assembled nanomaterials are finding a wide variety of applications in the area of nanotechnology, imaging techniques, biosensors, biomedical sciences, etc. due to its simplicity, spontaneity, scalability, versatility, and inexpensiveness. Self-assembly of amphiphiles into nanostructures (micelles, vesicles and hydrogels) happen due to various physical interactions. Recent advancements in the area of drug delivery have opened up newer avenues to develop novel drug delivery systems and self-assembled nanostructures have shown their tremendous potential to be used as facile and efficient materials for this purpose. The main objective of the projected review is to provide readers a concise and straightforward knowledge of basic concepts of supramolecular self-assembly process and how these highly functionalized and efficient nanomaterials can be useful in biomedical applications. Approaches for the self-assembly have been discussed for the fabrication of nanostructures. Advantages and limitations of these systems along with the parameters that are to be taken into consideration while designing a therapeutic delivery vehicle have also been outlined. In this review, various macro- and small-molecule-based systems have been elaborated. Besides, a section on DNA nanostructures as intelligent materials for future applications is also included.